Analisis Faktor yang Berhubungan dengan Turnover Perawat di Rumah Sakit Awal Bros Batam Tahun 2017 - Christiani, Luvi; Ilyas, Jaslis (UI Scholars Hub, 2018)
Hospitals as plenary health service providers have an obligation to maintain the quality of services provided. The nurse is one of the spearheads of service and is the largest part of the hospital's resources. The quality of nursing services with the main goal is to maintain patient safety by controlling the turnover rate. During 2015 to 2017 there were 15.4%, 14.3%, and 18.9% turnover rates for nurses at awal bros hospital batam. The method of research are quantitative and qualitative approach to determine factors related to nurse turnover. Quantitative research for all nurses who had left was 79 people. Qualitative research on nurses in the inpatient and critical care section with informants 7 people.Quantitative results with univariate statistical show nurses who had been turnover were 77.2% women and 22.8% men; 82.3% aged up to 30 years and 17.7% aged over 30 years; diploma level III 89.9 % and strata I 10.1%; married 55.7% and not married 44.3%; 62% of recruits came from outside Batam and 38% came from Batam; and working period up to 5 years 81% and working period above 5 years 19%. The bivariate statistical test showed that the factors associated with turnover were marital status (Asymp. Sig 0.003) and the area of recruitment (Asymp. Sig 0.000). Qualitative analysis with in depth interviews and focus group discussions found non-physical environmental factors, especially leadership problems lead to turnover. The turnover rate in Awal Bros Hospital Batam is still high with factors of marital status and area of recruitment, non-physical working environment that are associated with turnover. This can be taken into consideration as the Awal Bros Hospital Batam as a factor to be able to control nurse turnover.